2020
DOI: 10.1021/acs.inorgchem.9b02394
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Lattice Coupling Across the Magnetic Quantum-Phase Transition in Copper-Containing Coordination Polymers

Abstract: We measured the infrared vibrational properties of two copper-containing coordination polymers, [Cu­(pyz)2(2-HOpy)2]­(PF6)2 and [Cu­(pyz)1.5(4-HOpy)2]­(ClO4)2, under different external stimuli in order to explore the microscopic aspects of spin–lattice coupling. While the temperature and pressure control hydrogen bonding, an applied field drives these materials from the antiferromagnetic → fully saturated state. Analysis of the pyrazine (pyz)-related vibrational modes across the magnetic quantum-phase transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…The coupling constants for the two Fe-containing modes are on the order of −0.2 and −0.3 cm –1 , and that of the ammonium libration is an order of magnitude lower. These values are significantly smaller than the coupling constants of other molecule-based materials such as the low-dimensional copper halides across their magnetic saturation transitions . We attribute the difference to (i) through-space hydrogen- and halogen-bond exchange pathways in (NH 4 ) 2 [FeCl 5 ·(H 2 O)] as compared with superexchange pathways created by metal···ligand···metal linkages in low-dimensional quantum magnets and (ii) the value of the spin ( S = 5/2 for Fe 3+ vs 1/2 for Cu 2+ ) which determines the size of the spin–spin correlation function.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The coupling constants for the two Fe-containing modes are on the order of −0.2 and −0.3 cm –1 , and that of the ammonium libration is an order of magnitude lower. These values are significantly smaller than the coupling constants of other molecule-based materials such as the low-dimensional copper halides across their magnetic saturation transitions . We attribute the difference to (i) through-space hydrogen- and halogen-bond exchange pathways in (NH 4 ) 2 [FeCl 5 ·(H 2 O)] as compared with superexchange pathways created by metal···ligand···metal linkages in low-dimensional quantum magnets and (ii) the value of the spin ( S = 5/2 for Fe 3+ vs 1/2 for Cu 2+ ) which determines the size of the spin–spin correlation function.…”
Section: Resultsmentioning
confidence: 92%
“…We evaluate spin-phonon coupling across the magnetically driven phase transition at 30 T as ω = ω 0 + λ⟨ S i · S j ⟩ where ω and ω 0 are the perturbed and unperturbed phonon frequencies, λ is the mode-dependent spin-phonon coupling constant, and ⟨ S i · S j ⟩ is the nearest-neighbor spin–spin correlation function. The magnitude of λ quantifies how the magnetic exchange interaction J is modulated by the various phonon displacements. , Using the limiting low temperature value of ⟨ S i · S j ⟩ = S 2 = (5/2) 2 = 6.25, we calculate λ for several important distortions including the Fe–O stretch, the Fe–OH 2 rocking mode, and the NH 4 + twist near 60 cm –1 . These values are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing temperature (starting approximately at 400 mK) the phase transi- Both critical fields shift to higher values, when the applied magnetic field is tilted to the c direction (Fig. 8), so that for H ∥ c we obtained µ 0 H c1 = 4.80(5) T and µ 0 H c2 = 23.88(5) T. Interestingly, recent infrared spectroscopy studies of CPPP [41] showed pronounced changes in the pyrazine-related vibrational phonon spec- As mentioned, at H c1 the system undergoes a transition into the low-temperature TTL phase. Typically, upon decreasing temperature, 3D interactions become relevant, resulting in a field-induced magnetically ordered ground state.…”
Section: Magnetic Propertiesmentioning
confidence: 70%
“…The exchange interactions in structurally homologous, chemically similar materials can often vary widely, , offering an opportunity to design and investigate materials by finely tuning their geometries. Although an abundance of experimental information is available for these materials, , the factors that control the magnetic interactions are still debated. To be able to design materials with specific sets of magnetic interactions, these factors need to be understood in great detail.…”
Section: Introductionmentioning
confidence: 99%